2002
DOI: 10.1212/wnl.59.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil and flight simulator performance: Effects on retention of complex skills

Abstract: We report a randomized, double-blind, parallel group, placebo-controlled study to test the effects of the acetylcholinesterase inhibitor, donepezil (5 mg/d for 30 days), on aircraft pilot performance in 18 licensed pilots with mean age of 52 years. After 30 days of treatment, the donepezil group showed greater ability to retain the capacity to perform a set of complex simulator tasks than the placebo group, p < 0.05. Donepezil appears to have beneficial effects on retention of training on complex aviation task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
2
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 10 publications
0
93
2
5
Order By: Relevance
“…In our placebo-controlled study of donepezil, the drug group performed better on a set of complex flight simulator tasks than the placebo group after a 30-day treatment (Yesavage et al, 2002).…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 78%
See 2 more Smart Citations
“…In our placebo-controlled study of donepezil, the drug group performed better on a set of complex flight simulator tasks than the placebo group after a 30-day treatment (Yesavage et al, 2002).…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 78%
“…Study IIFDonepezil Study (Yesavage et al, 2002) This randomized, placebo-controlled, double-blind, parallel group study tested the effects of donepezil on flight simulator performance in 18 pilots. After being trained in the flight simulator, subjects were tested twice a day on each of 2 test days that were 30 days apart: baseline day and posttreatment day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such drug, donepezil, is already on the market and is approved by the U.S. Food and Drug Administration to treat memory loss. Indeed, one study found that pilots who took donepezil just before learning specific maneuvers in a flight simulator outperformed a control group on tests of performance conducted I month later (Yesavage et al 2002).…”
Section: The Availability and Use Of Psychological Enhancementsmentioning
confidence: 99%
“…Whether methylphenidate or other stimulants could decrease performance errors by those without the disorder or by physicians is an untested question. In another study, donepezil was shown to improve retention of training on complex aviation tasks among licensed pilots without dementia [6].…”
Section: The Case For Enhancementmentioning
confidence: 96%